Random non-proportional fatigue tests with planar tri-axial fatigue testing machine - T. Inoue; R. Nagao; N. Takeda (Fracture and Structural Integrity)
Complex stresses, which occur on the mechanical surfaces of transport machinery in service, bring a drastic degradation in fatigue life. However, it is hard to reproduce such complex stress states for evaluating the fatigue life with conventional multiaxial fatigue machines. We have developed a fatigue testing machine that enables reproduction of such complex stresses. The testing machine can reproduce arbitrary in-plane stress states by applying three independent loads to the test specimen using actuators which apply loads in the 0, 45, and 90 degree directions. The reproduction was tested with complex stress data obtained from the actual operation of transport machinery. As a result, it was found that the reproduced stress corresponded to the measured stress with an error range of less than 10 %. Then, we made a comparison between measured fatigue lives under random non-proportional loading conditions and predicted fatigue lives. It was found that predicted fatigue lives with cr, stress on critical plane, were over a factor of 10 against measured fatigue lives. On the other hand, predicted fatigue lives with ma, stress in consideration of a non-proportional level evaluated by using amplitude and direction of principal stress, were within a factor of 3 against measured fatigue lives